2022
DOI: 10.14202/vetworld.2022.1530-1534
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the nematode egg reappearance period in horses after anthelmintic therapy

Abstract: Background and Aim: Anthelmintics are used to control equine nematodes. However, helminth resistance to regularly used drugs is a well-known challenge. Among tests to assess effective control and monitor resistance, the most common is the fecal egg count reduction test (FECRT). In the absence of reliable FECRT results, the nematode egg reappearance period (ERP) is taken into account. This study aimed to examine horses from farms around the Moscow Region to assess nematode resistance through ERP after therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…[15] In this study, the overall prevalence of parasitic nematodes among examined equines was 70.25%. These ndings are nearly similar to the prevalence recorded by Baranova et al (2022) at 65%, [16] and lower than that investigated by Debere et al (2018) at 88.8%, [14] and Mathewos et al (2021;2022) at 78.5% and 94.5%, respectively. [17,18] Regarding the analysis of variables potentially associated with an increased risk of infection, the prevalence of intestinal helminths in donkeys is estimated to be higher (80%) than in working horses (56.25%).…”
Section: Discussionsupporting
confidence: 87%
“…[15] In this study, the overall prevalence of parasitic nematodes among examined equines was 70.25%. These ndings are nearly similar to the prevalence recorded by Baranova et al (2022) at 65%, [16] and lower than that investigated by Debere et al (2018) at 88.8%, [14] and Mathewos et al (2021;2022) at 78.5% and 94.5%, respectively. [17,18] Regarding the analysis of variables potentially associated with an increased risk of infection, the prevalence of intestinal helminths in donkeys is estimated to be higher (80%) than in working horses (56.25%).…”
Section: Discussionsupporting
confidence: 87%
“…The study of plant extracts and phytotherapy has increased due to the reduced efficacy of some commercial anthelmintics to control GIN, which may evolve into anthelmintic resistance (AR) in part due to the overuse of these drugs to maintain animal productivity [2,3,27]. Besides this, the search for secondary metabolites derived from essential oils is important in equine nematodes because they promote one health considering that these species share some pathogens, niche adaptation, epidemiology, vector transmission, culture resources, food safety and biosecurity with humans [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most known genera include the small strongyles or cyathostomins (Trichonema, Cyalocephalus, Cyathostomum and Gyalocephalus) and large strongyles (Strongylus and Triodontophorus), which are responsible for mild to severe clinical injury [16,17]. Control of these nematodes involves commercial anthelmintic drugs which are administered to reduce the impact of parasites on animal health and improve their productivity [2]. However, the overuse of different drugs has been pointed as a cause of anthelmintic resistance (AR) identified in the main GIN species, causing low effectiveness [27], thus sustainable control alternatives have been required [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that the ERP in IVM-treatment is typically 8-13 weeks [35][36][37]. However, recent studies have indicated a reduced ERP 6-8 weeks after treatment [38,39]. The rationale behind this phenomenon may be attributed to an increased selection pressure for resistance development in specific species or a potential reduction in the efficacy of anthelmintics against the luminal stages of cyathostomins [32].…”
Section: Introductionmentioning
confidence: 99%